Comparative Analysis of Superindo Supermarket Financial Performance Before and After the Pandemic - Misidawati, Dwi Novaria; Santoso, Aprih; Zanbaina, Ghafira (Universitas Proklamasi 45, 2024)
This research aims to recognize the monetary performance before and during the Covid-19 pandemic at Superindo Supermarkets. This study uses quantitative strategies compared with the Kruskal Wallis take examine economic overall performance. This research suggests variations in liquidity, solvency, profitability, and economic sports. Superindo grocery store before and throughout the Covid-19 pandemic. This difference is because of nature conservative in the supermarket to develop business and allocate funding to gadgets or sectors that don't have danger tall. This condition causes many efficiencies to occur with terminating or lessening employment worker salaries which affects on shopping strength public. A decrease in human beings's shopping power and mobility regulations create sales the organization declines. This research does now not discover the difference between liquidity ratios with the contemporary ratio and quick ratio. This result permits the use of measurements of different liquidity together with the coins turnover ratio because it shows the relative cost among values of internet sales with internet working capital.